The diagnostic challenge of psychiatric symptoms in neurodegenerative disease; rates of and risk factors for prior psychiatric diagnosis in patients with early neurodegenerative disease - Woolley, Josh D. (2011)
OBJECTIVE: To identify rates of and risk factors for psychiatric diagnosis preceding the diagnosis of neurodegenerative disease (ND). METHOD: Systematic, retrospective, blinded chart review of patients with a ND diagnosis [behavioral variant frontotemporal dementia (bvFTD n=69); Alzheimer’s disease (AD n=65); semantic dementia (SemD n=41); progressive non-fluent aphasia (PNFA n=17); corticobasal degeneration (n=25); progressive supranuclear palsy (n=15); and amyotrophic lateral sclerosis (ALS n=20)]. RESULTS: 28.2% of patients with a ND received a prior psychiatric diagnosis. Depression was the most common psychiatric diagnosis in all groups. BvFTD patients received a prior psychiatric diagnosis significantly more often (52.2%) than patients with AD (23.1%), SemD (24.4%), or PNFA (11.8%), and were more likely to receive diagnoses of bipolar affective disorder or schizophrenia than patients with other NDs (p<0.001). Younger age, higher education and a family history of psychiatric illness increased the rate of prior psychiatric diagnosis in patients with bvFTD (p<0.05). Cognitive, behavioral and emotional characteristics did not distinguish patients who did and did not receive a prior psychiatric diagnosis. CONCLUSION: ND is often mistaken for psychiatric disease with bvFTD patients at highest risk for misdiagnosis. Because psychiatric misdiagnosis can lead to delayed and inappropriate treatment, and family and patient distress, physicians should consider referring mid- to late-life patients with new onset neuropsychiatric symptoms for ND evaluation.